Life-history strategy, adverse environment, and justification of life-ending decisions - Guo, Shaolingyun; Lu, Hui Jing (Frontiers in Psychology, 2025)
ObjectiveEvidence remains limited regarding the interplay between childhood environment, as reflected by life-history calibration, and the current environment, as well as their combined influence on cognitive judgments about life-ending decisions. Drawing on life-history theory, the present study aims to (1) examine whether life-history trade-offs along the fast-slow continuum are associated with the subjective justification of suicide and assisted suicide (euthanasia practices), and (2) explore whether the current environment moderates this relationship.MethodsIn Study 1, a vignette-based questionnaire was administered to Chinese young adults (N = 147) to examine the relationships among life-history traits, current environmental adversity, and the subjective justification of life-ending behaviors. In Study 2, these hypotheses were further tested using cross-national data from the World Values Survey (N = 6,766). Structural equation modeling was employed in both studies to analyze the proposed associations.ResultsFindings from Study 2 indicated that individuals who adopted a slow life-history strategy were less likely to subjectively justify life-ending behaviors. Furthermore, results from both studies demonstrated that the relationship between life-history strategy and the justification of life-ending decisions was moderated by current environmental adversity.ConclusionThese findings underscore the influence of life-history orientation on cognitive judgments related to life-ending decisions and highlight the moderating role of current environmental conditions. Implications for future suicide intervention programs are discussed.